2014
DOI: 10.1523/jneurosci.3418-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Tau-Mediated NMDA Receptor Impairment Underlies Dysfunction of a Selectively Vulnerable Network in a Mouse Model of Frontotemporal Dementia

Abstract: Frontotemporal dementia (FTD) is a neurodegenerative behavioral disorder that selectively affects the salience network, including the ventral striatum and insula. Tau mutations cause FTD, but how mutant tau impairs the salience network is unknown. Here, we address this question using a mouse model expressing the entire human tau gene with an FTD-associated mutation (V337M). Mutant, but not wild-type, human tau transgenic mice had aging-dependent repetitive and disinhibited behaviors, with synaptic deficits sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 48 publications
4
51
0
Order By: Relevance
“…depletion of synaptic vesicle pool) and function of the mossy fibers, which also affected postsynaptic neurons [41]. Mice expressing the V337M mutant of Tau showed an NMDA receptor hypofunction, and pathology could be prevented by the NMDAR co-agonist cycloserine [42]. These and previous studies (for review see e.g.…”
Section: Pathological Tau Reduces Network Activitysupporting
confidence: 56%
“…depletion of synaptic vesicle pool) and function of the mossy fibers, which also affected postsynaptic neurons [41]. Mice expressing the V337M mutant of Tau showed an NMDA receptor hypofunction, and pathology could be prevented by the NMDAR co-agonist cycloserine [42]. These and previous studies (for review see e.g.…”
Section: Pathological Tau Reduces Network Activitysupporting
confidence: 56%
“…It was shown that a transgenic mouse model overexpressing mutant human tau exhibits spontaneous epileptic activity and seizures with spike-wave complexes in the EEG recordings, and a higher sensitivity to PTZ (García-Cabrero et al, 2013). Additionally, reduction of endogenous tau was shown to ameliorate network hyperexcitability and cognitive impairment in transgenic APP mice (Roberson et al, 2007, 2011; Warmus et al, 2014; Hall et al, 2015). Conversely, a recent study showed that hyperphosphorylated tau reduces hippocampal CA1 neuronal hyperexcitability via relocation of the axon initial segment down the axon in P301L tau transgenic mice (Hatch et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated plus maze has been used in a PGRN deficiency, a CHMP2B mutant and a tau-based mutant transgenic model of bvFTD. In these three studies, mice spent more time in the open arms, showing a disinhibited behavior [29,30,31]. The light/dark box test showed opposite results in two studies based on mice expressing two different tau mutations (P301L and R406W): one line showed disinhibited behavior [32], and the other showed no defect [33].…”
Section: The Ftd Symptoms and Corresponding Tests In Micementioning
confidence: 99%
“…It is used as a test of motivation in depression studies [42]. Recently, this test has been used in a study describing deficits in nest building in mice expressing a tau mutant [31]. …”
Section: The Ftd Symptoms and Corresponding Tests In Micementioning
confidence: 99%
See 1 more Smart Citation